1993
DOI: 10.1002/eji.1830231144
|View full text |Cite
|
Sign up to set email alerts
|

Antigens pre‐bound to the primate erythrocyte complement receptor via cross‐linked bispecific monoclonal antibody heteropolymers are rapidly cleared from the circulation

Abstract: We have used cross-linked, bispecific monoclonal antibody heteropolymers, specific for primate erythrocyte (E) complement receptor (CR1) and target antigen (Ag), to attach 125I-labeled Ag to 51Cr-labeled monkey erythrocytes (E) in vitro. Injection of these sensitized E into monkeys leads to rapid clearance from the circulation of several different 125I-labeled Ag with little, if any sequestration, lysis, or clearance of the E. It should now be possible, in principle, to use the heteropolymer-E system to facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Next, ICs are cleared from liver or spleen (Davies et al 1990). Transfer of the ICs to liver or spleen phagocytes leads to IC destruction but generally occurs without harm to the erythrocytes that are recycled (Birmingham and Hebert 2001;Cosio et al 1981;Cosio, Sedmak, and Nahman 1990;Hebert, Birmingham, Mahan, et al 1994;Reist et al 1993).…”
Section: Ic Clearance Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, ICs are cleared from liver or spleen (Davies et al 1990). Transfer of the ICs to liver or spleen phagocytes leads to IC destruction but generally occurs without harm to the erythrocytes that are recycled (Birmingham and Hebert 2001;Cosio et al 1981;Cosio, Sedmak, and Nahman 1990;Hebert, Birmingham, Mahan, et al 1994;Reist et al 1993).…”
Section: Ic Clearance Mechanismsmentioning
confidence: 99%
“…Experimentally, cross-linked mAb complexes (e.g., bispecific antibodies that recognize CR1 as well as an unrelated antigen) also bind to CR1 for clearance by liver and spleen phagocytic cells (Edberg, Kimberly, and Taylor 1992;Nardin, Lindorfer, and Taylor 1999;Reist et al 1993;Taylor et al 1992;Taylor, Ferguson, et al 1997). IgG dimers present in therapeutic intravenous immunoglobulin (IVIg) drugs also activate complement, acquire C3b deposits, and bind to CR1 (Shoham-Kessary, Naot, and Gershon 1998).…”
Section: Ic Clearance Mechanismsmentioning
confidence: 99%
“…Previously, we reported that "partial heteropolymers," biotinylated anti-CR1 MAb mixed with SA, bind in vivo to erythrocytes of rhesus monkeys but are not cleared from the circulation (25). However, complete heteropolymers, containing MAb to CR1 cross-linked with either human or mouse IgG, bind to primate erythrocytes and are cleared (26). Numerous in vivo studies indicate that IgG that is bound to erythrocytes via cell surface antigens causes the erythrocyte to be recognized and cleared by the RES (45,46), yet IgG that is bound to erythrocyte CR1 as part of a C3b-opsonized IC does not sensitize erythrocytes for clearance, but IC are cleared and removed from erythrocytes in the liver and spleen (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…MAb 1B4 (also anti-CR1) and HB43 (anti-human IgG) have been characterized previously (3 1-33). Anti-CRl MAb were conjugated with biotin at combining molar ratios of 10 biotins per MAb (26,34). MAb were labeled with 1251 by the iodogen method (35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation